2001
DOI: 10.1603/0022-0493-94.6.1445
|View full text |Cite
|
Sign up to set email alerts
|

Bollworm (Lepidoptera: Noctuidae) Survival on ‘Bollgard’ and ‘Bollgard II’ Cotton Flower Bud and Flower Components

Abstract: Genetically modified cotton, Gossypium hirsutum L., cultivars ('Bollgard') that produce crystalline proteins from Bacillus thuringiensis (Berliner) are valuable tools for managing lepidopteran insect pests in the United States. However, high numbers of bollworm, Helicoverpa zea (Boddie), larvae have been observed feeding in white flowers of these cultivars. Fresh tissue bioassays were conducted to investigate bollworm survival on Bollgard and 'Bollgard II' cottons. Bollworm survival was higher on square and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 8 publications
6
81
1
5
Order By: Relevance
“…Holt (1998) correlated this decline in Bollgard cultivars to increased survival of H. armigera. Furthermore, season-long differences in expression among cultivars can vary as much as 2-fold throughout the season , and plant structures, such as terminal leaves, express more Cry1Ac compared with certain flower structures (Greenplate, 1999;Greenplate et al, 2000;Gore et al, 2001). Therefore, control strategies may be further compromised by the differential expression of Cry1Ac among plant structures and cultivars that create a spatial source for survivors to develop.…”
mentioning
confidence: 99%
“…Holt (1998) correlated this decline in Bollgard cultivars to increased survival of H. armigera. Furthermore, season-long differences in expression among cultivars can vary as much as 2-fold throughout the season , and plant structures, such as terminal leaves, express more Cry1Ac compared with certain flower structures (Greenplate, 1999;Greenplate et al, 2000;Gore et al, 2001). Therefore, control strategies may be further compromised by the differential expression of Cry1Ac among plant structures and cultivars that create a spatial source for survivors to develop.…”
mentioning
confidence: 99%
“…In the United States, the level of resistance of cotton with Cry1Ac genes has been raised by expressing additional genes from B. thuringiensis, in particular the Cry2Ab and Cry1F genes (Tabashnik et al 2009). Generally, these double gene varieties have signiÞcantly higher levels of resistance than single-gene varieties expressing Cry1Ac only , Gore et al 2001, Stewart et al 2001. The comparatively strong effect of the additional gene on the resistance level in these double gene varieties would suggest that these genes might complement the effect of the Cry1Ac gene more effectively than the CpTI gene does.…”
Section: Discussionmentioning
confidence: 99%
“…Some other field studies have shown that there were no significant differences in larval density among Bt and non-Bt cotton [112,113]. As Bt cotton varieties expressing single toxin gene (Cry1Ac) have no resistance against armyworm, Spodoptera species, to overcome this problem a Bollgard ® II cotton was developed that contain Cry1Ac and Cry2Ab, which provide the adequate control of armyworm and cotton bollworms [114][115][116][117][118][119][120][121][122][123].…”
Section: Armyworm (Spodoptera Spp)mentioning
confidence: 99%